2021
DOI: 10.3389/fonc.2021.657024
|View full text |Cite
|
Sign up to set email alerts
|

Nivolumab and Hypofractionated Radiotherapy in Patients With Advanced Lung Cancer: ABSCOPAL-1 Clinical Trial

Abstract: BackgroundMore clinical practice need to be performed to verify the toxicity of the hypofractionated radiotherapy (HFRT) combined with PD-1 blockade in lung cancer. This phase I study aimed to investigate the safety and efficacy of nivolumab combined with HFRT in patients with progressive advanced lung cancer following multiline treatment.MethodsWe enrolled 31 patients with advanced lung cancer pathologically confirmed to have progressive disease and treated with first-line or a higher therapy. Selected lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 23 publications
0
12
0
1
Order By: Relevance
“…The overall objective response and complete remission rates were 39.13% and 13.04%, respectively. The 1-year OS and median progression-free survival were 60.9% and 6 months, respectively ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…The overall objective response and complete remission rates were 39.13% and 13.04%, respectively. The 1-year OS and median progression-free survival were 60.9% and 6 months, respectively ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, the overall objective response and complete remission rate were 39.13% and 13.04%, respectively [17]. CR patients maintained continuous remission for a 2yearfollow-up period.…”
Section: Introductionmentioning
confidence: 85%
“…Clinical response was assessed using computed tomography (CT) scans according to the Response Evaluation Criteria for Solid Tumors (RECIST V1.1) and classifed as partial response (PR), stable disease (SD), or progressive disease (PD). Further details are provided in our previous report [17]. Interpretation of response from positron emission tomography (PET) scans was based on the European Organization for Research and Treatment of Cancer 1999 standard [19].…”
Section: Assessment Of Tumor Volume and Clinical Responsementioning
confidence: 99%
“…Exclusion criteria were ( 1 ) single-arm studies, ( 2 ) reviews/comments/letters, ( 3 ) meeting abstracts, ( 4 ) IT plus SBRT versus SBRT studies, ( 5 ) study protocols, ( 6 ) case reports, and ( 7 ) retrospective studies. Any disagreements were resolved by discussion.…”
Section: Methodsmentioning
confidence: 99%
“…In a phase 1 trial reported by Bestvina, IT combined with SBRT showed a 46% objective response rate (ORR) with a median progression-free survival (PFS) of 5.8 months in widely metastatic NSCLC patients ( 5 ). In another phase 1 trial reported by Ye, the ORR was 39% and the median PFS was six months when advanced lung cancer patients were treated with IT plus SBRT ( 6 ). Moreover, several case studies indicated that some advanced patients achieved long-term survival after IT and SBRT ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%